Changes in patterns of plastic surgery emergencies at a level I trauma center in India during the COVID-19 pandemic - Veena Singh; Ansarul Haq; Sarsij Sharma; Sanjeev Kumar; Aditya Kumar; Amarjeet Kumar; Neeraj Kumar; Anil Kumar (Journal of Trauma and Injury)
Purpose The coronavirus disease 2019 (COVID-19) pandemic has had major effects worldwide, including sudden and forceful setbacks to the healthcare system. The COVID-19 pandemic has also led to changes in the plastic and reconstructive management of emergency cases, including those due to road traffic accidents. This study analyzed changes in patterns of plastic surgery emergencies and modifications in consultation policies to minimize the exposure of healthcare workers. Methods Data on plastic surgery emergency calls received from the trauma and emergency department were collected for a period of 2 months before and during lockdown. The data were then analyzed with respect to the cause, mechanism, and site of the injury, as well as other variables. Results During lockdown, there was a 40.4% overall decrease in the plastic surgery emergency case volume (168 vs. 100). The average daily number of consultations before lockdown was 2.8 as compared to 1.6 during lockdown. Road traffic accidents remained the most common mechanism of injury in both groups (45.8% vs. 39.0%) but decreased in number during the lockdown (77 vs. 39). Household accidents, including burns, were the second most common cause of injury in both phases (7.7% vs. 20.0%), but their proportion increased significantly from 7.7.% to 20.0% in the lockdown phase (P=0.003). The percentage of minor procedures done in the emergency department increased from 53.5% to 72.0% during lockdown (P=0.002). Procedures in the operating room decreased by 73.1% during lockdown (67 vs. 18, P=0.001). Conclusions The COVID-19 pandemic and lockdown orders in India greatly influenced trends in traumatic emergencies as observed by the plastic surgery team at our tertiary care center. Amidst all the chaos and limitations of the pandemic period, providing safe and prompt care to the patients presenting to the emergency room was our foremost priority.